A case study on crack propagation law of cement stabilised macadam base. Issue Volume 21:Issued 4(2020) (20th March 2020) - Gao, Junqi; Jin, Peipei; Sheng, Yuxiang; An, Ping
ABSTRACT: Based on the indoor crack monitoring test, the feasibility of monitoring base crack with sensing optical fibre and the appropriate optical fibre category are studied in detail. Through the field monitoring test of cement stabilised macadam, the crack development law in the early stage of cement stabilised base layer was researched. The test results show that the proposed sensing fibre can be used in researching the crack development law of cement stabilised macadam base. The initiation of crack in cement stabilised macadam base occurs mainly in the first 3 days after construction, in which the dry shrinkage crack is dominant. The development of the dry shrinkage probably ended in about 30 days. The dry shrinkage stress is the main factor of crack initiation and crack spacing. The influence of thermal stress on early crack spacing is very weak, and the thermal stress strongly affects the crack width. The thermal cracks basically appear in the location where the dry shrinkage stress displays peaks during the dry shrinkage phase. When the subbase and base layers were constructed continuously, the transverse cracks in cement stabilised macadam are always penetrating cracks.